Linking Jasmonic Acid Signaling, Root Exudates, and Rhizosphere Microbiomes - Carvalhais, Lilia C.; Dennis, Paul G.; Badri, Dayakar V.; Kidd, Brendan N.; Vivanco, Jorge M.; Schenk, Peer M. (Molecular plant-microbe interactions, 2015)
Jasmonic acid (JA) is an essential hormone in plant development and defense responses in Arabidopsis thaliana. Exogenous treatment with JA has recently been shown to alter root exudate profiles and the composition of root-associated bacterial communities. However, it is currently unknown whether disruptions of the JA in the rhizosphere affect root exudation profiles and the relative abundance of bacteria and archaea in the rhizosphere. In the present study, two Arabidopsis mutants that are disrupted in different branches of the jasmonate pathway, namely myc2 and med25, were cultivated in nutrient solution and soil to profile root exudates and bacterial and archaeal communities, respectively. Compared with the wild type, both mutants showed distinct exudation patterns, including lower amounts of asparagine, ornithine, and tryptophan, as well as distinct bacterial and archaeal community composition, as illustrated by an increased abundance of Streptomyces, Bacillus, and Lysinibacillus taxa in the med25 rhizosphere and an Enterobacteriaceae population in myc2. Alternatively, the Clostridiales population was less abundant in the rhizosphere of both mutants. Similarities between plant genotypes were highly correlated, as determined by operational taxonomic units in the rhizosphere and metabolites in root exudates. This strongly suggests that root exudates play a major role in modulating changes in microbial community composition upon plant defense responses.